Postpartum depression in the Occupied Palestinian Territory: a longitudinal study in Bethlehem. Issue 1 (December 2016) - Qandil, Sara; Jabr, Samah; Wagler, Stefan; Collin, Simon
Abstract Background Postpartum depression (PPD) affects women from different cultures around the world. No previous studies have investigated PPD among women in Palestine. Fertility rates in Palestine are among the highest in the world, hence even low rates of PPD could have considerable national impact. The aim of this study was to determine the prevalence of, and risk factors for, PPD among Palestinian mothers. Methods 101 mothers were recruited during the registration of their child's birth (within 1 week) at the Bethlehem branch of the Ministry of Interior. Participants were assessed via a face to face interview, and were followed up 1 week, 2 weeks, 6 weeks, 3 months, and 6 months later by telephone interview. Interviews included the Arabic Edinburgh Postnatal Depression Scale (EPDS), with PPD indicated by depressive symptoms (EPDS score ≥11) at ≥2 follow-up time points. Pearson's correlation was calculated between repeated EPDS scores, and multivariable logistic regression was used to investigate risk factors for PPD. Results The prevalence of depressive symptoms was fairly constant (14–19%) over the follow-up period. Most depressive symptoms developed within 1 month of delivery; mothers with depressive symptoms at 3 months postpartum were highly likely to still have symptoms at 6 months. 27.7% (28/101) of women met our criteria for PPD. High parity (odds ratio (OR) 4.52 (95% CI 0.90, 22.8) parity 3+versus primiparous), unplanned pregnancy (OR 2.44 (0.99, 6.01)) and sex of child not being the one desired (OR 5.07 (1.12, 22.9)) were associated with PPD, but these associations were attenuated in multivariable analysis. Conclusions The prevalence of PPD in Palestine appears to be higher than in high income countries, but similar to the prevalence in other Middle Eastern countries. High parity and unplanned pregnancy were identified as risk factors for PPD, suggesting that fully meeting the need for family planning could reduce the incidence of PPD in the Palestinian population.